Phylogenetic relationship and characterization of the complete chloroplast genome of the alpine leaf-warbler in Qinghai-Tibet Plateau. Issue 2 (3rd July 2019) - Liu, Zhenhao; Liu, Jinlong; Chen, Xiangwu; Jin, Zhenyu; Luo, An; Li, Shaobin
Abstract: The Alpine Leaf-warbler ( Phylloscopus occisinensis ) is a small-sized and poorly-known songbird endemic to China. In this study, we sequenced and described the whole mitochondrial genome of the Alpine leaf-warbler. The entire mitochondrial sequence was determined by long-range PCR and conserved primer walking approaches. The results demonstrated that the whole mitochondrial genome of P. occisinensis was 16, 879 bp in length with 53.1% A + T content; the genome harboured the same gene order as that of other passerine birds, including 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and non-coding control region. The control region (D-loop) of P. rubicilloides include two portions that one was located between tRNA-Gln and tRNA-Phe (219 bp in length) and the other is between tRNA-Thr and tRNA- Pro (1087 bp in length), which is similar to other Leaf-warblers. Phylogenetic analysis indicated that the genome of Phylloscopus species clustered within a clade and is closer related to Aegithalidae species than Paridae species. These mitochondrial data are potentially important for the further studies on molecular evolution and conservation genetics on leaf warbler species.